Fabrication of buckypaper with tailored porosity for application in water filtration - Elnur, Ruaa (AUC Knowledge Fountain, 2016)
The rapid development in membrane technologies and their use as a filtration medium have been based on the use and development of new materials to improve system performance. Carbon nanotubes (CNTs) represent a class of promising nanomaterial, exhibiting outstanding mechanical, electrical, thermal conductivity and adsorption properties. The idea of using carbon nanotubes in the separation and filtration industry has been put forward, but constructing macroscopic structures with controlled density, porosity, and morphology has been a challenge. Buckypaper (BP) is a form of CNT film that is being investigated for application in water treatment. In BPs, the CNTs are oriented randomly into non-woven or paper like structure. This arrangement helps provide a large specific area with highly porous three dimensional network structures. However, the preparation of BP membranes with controlled porosity and pore size distribution entails taking into account many processing parameters. Porosity is a key property for the use of BPs in separation applications in general. The work conducted here aims at preparing BPs with controlled porosity through the investigation of three different parameters, which impact porosity. These entail the porosity of the supporting filter membrane during the preparation of the BPs, as well as the exposure of prepared BPs to different solvents vapors and for different exposure times. The retention performance of the obtained BPs in water filtration is tested using micro-sized polymer beads. CNT-BPs were prepared using vacuum filtration. Morphology and pore size distribution were investigated using scanning electron microscopy (SEM), nitrogen gas adsorption and mercury porosimetry. Different parameters were evaluated for their effect on tailoring the porosity of BPs. Statistical analysis was used to determine the effect of the three parameters investigated, namely (1) the pore size of the membrane filter used in the preparation of BPs from CNT dispersions, (2) type of solvent vapors to which the prepared BPs are exposed, and (3) the exposure time to the solvent vapors, on the final membrane porosity. Results indicated that the type of solvent affects the pore size distribution with DMF giving more pores in the smaller pore size ranges. In addition, variation of pore size distribution of the BP membranes was observed upon varying the pore size of the membrane filter. On the other hand, no significant change was detected on changing the time exposure to the boiling solvent. One variable and one combination of variables were found to be successful in producing BPs with a lower average pore size. The findings confirm the potential of the solvent evaporation technique in tailoring the porosity of BP and membranes for filtration applications. Finally, obtained BPs were tested for water filtration applications. Polystyrene beads of size ranges 0.3 µm and 0.6 µm, were chosen as model for bacteria and colloids removal, respectively. A comparison between blank BPs and modified BPs (subjected to solvent vapor for 40 minutes and prepared on specific membrane filter) was conducted. For the 0.3 µm of polystyrene beads, the blank BP showed a retention percentage of about 71% in comparison to the modified one which had a retention percentage of about 73%. For the 0.6 µm of polystyrene beads, the blank BP showed a retention percentage of about 67%, while the modified one had a percentage of about 75%. This indicates that the modified BPs possess smaller pore sizes on average than unmodified BP.